Kemampuan Literasi dan Kepercayaan Diri Siswa SMP Berdasarkan Akreditasi Sekolah Swasta dan Negeri di Kota Singkawang - Zulfahita Zulfahita; Nurul Husna; Sri Mulyani (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
This study aims to describe literacy skills, both mathematical literacy, and language literacy, as well as the self-confidence of junior high school students based on public and private school accreditation. The research method used was a descriptive qualitative. The subjects of this study consisted of 169 students from 7 randomly selected schools. The instruments used were mathematical literacy questions, language literacy questions, and self-confidence questionnaires which were supported by interviews. The data analysis technique used qualitative descriptive analysis. Based on the results of data analysis, it can be concluded: (1) Mathematical literacy skills at state schools with A accreditation were sufficiently able to apply the processes of communication literacy, representation, reasoning, and arguments, devising strategies for solving problems, symbols and formalism. Mathematical literacy at state schools with B accreditation was quite capable of implementing the Mathematising Representation literacy process and devising strategies for solving problems. Mathematical literacy in private schools with A accreditation was quite capable of implementing the devising strategies for solving problems literacy process. And, Mathematical literacy in private schools with B accreditation was quite capable of implementing the communication literacy process. (2) Language literacy skills in public and private schools with A and B accreditation showed the same ability. (3) The self-confidence level of students, both public and private schools based on accreditation A and B, was in the sufficient category, and contributed to students confidence and the quality of education.